Investigation on deformation of composite multi-bolted joints considering influences of hole-location errors and installation sequence. (October 2022) - Liu, Chinan; Li, Yuan; Cheng, Yi; Li, Ximing; Cao, Sipeng; Cheng, Hui; Luo, Bin
Highlight: Hole-location error leads to deformation of composite joints which distributed symmetrically along direction of the error. Forced connection causes non-uniform deformation of exit and damage on surface and hole of joints. Average deformation can be reduced by more than 70% after changing installation sequence form middle to both sides. Abstract: In this paper, deformation of composite multi-bolted joints considering hole-location error and installation sequence was investigated. Experiments were conduct to examine deformation and damage of joints with different hole-location error and installation sequence. Deformation of joints was measured by laser measurement system. Bolt-composite interfaces were examined microscopically to reveal damage caused by forced installation. Results showed that hole-location error caused vertical deformation of composite joint. Non-uniform extrusion of up and down hole was caused by forced installation. Besides, deformation mode of hole exit was dominated by deformation asymmetry. Damage distribution was influenced by radial extrusion direction of up and down holes. Thus, damage was distributed no-uniformly along depth of holes. During forced installation, deformation accumulation of multi-bolted joints was generating. Different installation sequences caused various deformation distribution of composite joints. Average deformation were reduced by more than 70% after changing the installation sequence. Conclusions of this paper are of significance for developing deformation model and deformation reduction of composite multi-bolted joints assembly.